Visual design solutions - Malamed, Connie (Wiley, 2015)
No matter what medium you use to deliver content, if the visual design fails, the experience falls flat. Meaningful graphics and a compelling visual design supercharge instruction, training, and presentations, but this isn't easy to accomplish. Now you can conquer your design fears and knowledge gaps with Visual Design Solutions: a resource for learning professionals seeking to raise the bar on their graphics and visual design skills. This informal and friendly book guides you through the process and principles used by professional graphic designers. It also presents creative solutions and examples that you can start using right away. Anyone who envisions, designs, or creates instructional or informational graphics will benefit from the design strategies laid out in this comprehensive resource